THE INFLUENCE OF PRINCIPAL’S LEADERSHIP AND TEACHER PROFESSIONAL COMPETENCY TOWARD STUDENTS’ LEARNING ACHIEVEMENTS) - Dekawati, Ipong; Istianah, Anah (Universitas Pendidikan Indonesia, 2018)
The purpose of this research is to find out and examine the influence of principal's leadership and teacher’s professional competency toward students’ learning achievement. The research method was descriptive and verification methods, with a Likert scale questionnaire as data collection techniques distributed to 54 teachers. Regression analysis technique was used in processing the research result with F-Test as the significance test. The results showed that: (1) there was a positive but less significant effect between the leadership of the principal on students’ achievement. (2) There is a positive and significant influence between the professional competencies of teacher on students’ achievement. (3) There is a positive and significant influence between the principal's leadership and teacher professional competence simultaneously on the learning achievement. Starting from these conditions, the authors suggest, that: (1) Principals are expected to be able to implement their mission more optimally by involving teachers in the preparation of vision and mission as well as improving their socialization programs to have whole understanding from all elements in the school (2) Teachers should learn more and comply with ethics code by attending the MGMP discussion and PGRI meetings. The teachers also have to maximize and enrich their teaching materials, by reading more journals and books in accordance with their fields and delving more insight from the internet.